ANALYSIS OF SCIENTIFIC PRODUCTION IN DISSERTATIONS AND THESES WITH FOCUS ON RESOURCE ROOMS OPERATION - Aline Costa Fantinato; Enicéia Gonçalves Mendes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The aim of this study analysis was of scientific production in the form of theses and dissertations related to resource rooms operation. For that, it was done a research in Capes theses and dissertations database with the following descriptors: specialized educational services, resource rooms and multifunctional resource rooms, which resulted in 33 studies published on this subject. The results indicate that there are possibilities and problems in these services, and that the MRR can be a resource, but by itself cannot attend the needs of all Special Education target audience students. This study aimed to contribute to the investigation of the National Centre for Special Education and consequently with important data about resource rooms operation in the country, making it possible to know how this environment has represented and being presented in academic research, as also for to build the state of the art on the specialized educational services  in multifunctional resource rooms.